Genotype x Environment Interaction and Yield Stability of Several Yield Components Among Adapted Rice Cultivars in West Sumatra - Aslim Rasyad; Azwir Anhar (Zuriat, 2007)
Genotype by environment (GE) interaction and genotype stability of a trait in rice (Oryza sativa L.) are very important for plant breeders in making decision regarding the development and evaluation of new cultivars as well as for farmers in selecting suitable cultivars to be planted for commercial purpose. Yield components including panicles number plant–1, number of grains panicle–1, 1000-grain weight, and grain yield of five locally adapted cultivars of rice were evaluated at three locations in West Sumatera. The data were used to determine GE interaction variance components and stability of the traits. There were significant effects of locations on yield and some yield components except number of panicles plant–1. The cultivars differed significantly in all yield components but not in grain yield. The influence of GE interaction was highly significant on all yield components and grain yield. The magnitude of GE interaction variance component was greater than that of location for all traits. These data suggested that genotypes performed differently among the locations and were not stable with respect to the locations, so that farmers should select a suitable cultivar to be grown in the area of production.